Effects of dietary turmeric administration on stress, immune, antioxidant and inflammatory responses of common carp (Cyprinus carpio) during copper exposure - Hamid Rajabiesterabadi (2020)
© 2020 John Wiley & Sons Ltd The present study assessed the effects of dietary turmeric on Cyprinus carpio resistance and responses to copper exposure. First, the fish were assigned to four treatments received diets supplemented with 0 (control), 5, 10 and 20 g/kg turmeric for 3 weeks. Thereafter, the fish were exposed to lethal concentration (3.5 mg/L) of ambient copper for 24 hr and mortality was 65.3%, 41.8%, 22.7% and 20.6%, respectively. In the second experiment, the fish were fed with the aforementioned diets and simultaneously exposed to sub-lethal concentration (0.25 mg/L) of ambient copper for 3 weeks. Copper exposure led to increases in plasma cortisol, glucose, malondialdehyde (MDA), alanine transaminase (ALT) and aspartate transaminase (AST), and decrease in plasma T4, T3, lysozyme, alternative complement haemolytic (ACH50), bactericidal activities, superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and blood red blood cell count (RBC) and haemoglobin. Moreover, copper exposure led to significant upregulation of tumour necrosis factor-alpha (TNF-a) and interleukin 1-beta (IL1-b), and significant downregulation of interleukin 10 (IL10) gene expressions in the fish liver. Turmeric administration at 10 g/kg significantly mitigated/inhibited the copper-induced negative effects, which seems to be due to the augmenting of the antioxidant defence.